Prediction of Metabolic Interactions With Oxycodone via CYP2D6 and CYP3A Inhibition Using a Physiologically Based Pharmacokinetic Model. (17th December 2014) - Marsousi, N; Daali, Y; Rudaz, S; Almond, L; Humphries, H; Desmeules, J; Samer, C F
Abstract : Evaluation of a potential risk of metabolic drug–drug interactions (DDI) is of high importance in the clinical setting. In this study, a physiologically based pharmacokinetic (PBPK) model was developed for oxycodone and its two primary metabolites, oxymorphone and noroxycodone, in order to assess different DDI scenarios using published in vitro and in vivo data. Once developed and refined, the model was able to simulate pharmacokinetics of the three compounds and the DDI extent in case of coadministration with an inhibitor, as well as the oxymorphone concentration variation between CYP2D6 extensive metabolizers (EM) and poor metabolizers (PM). The reliability of the model was tested against published clinical studies monitoring different inhibitors and dose regimens, and all predicted area under the concentration–time curve (AUC) ratios were within the twofold acceptance range. This approach represents a strategy to evaluate the impact of coadministration of different CYP inhibitors using mechanistic incorporation of drug‐dependent and system‐dependent available in vitro and in vivo data. CPT Pharmacometrics Syst. Pharmacol. (2014) 3, e152; doi:10.1038/psp.2014.49 ; published online 17 December 2014